Renewable Energy Development and Employment in Ecuador’s Rural Sector: An Economic Impact Analysis - Ulloa-de Souza, Raúl Clemente; González-Quiñonez , Luis Adrián; Reyna-Tenorio, Luis Jheovanny; Salgado-Ortiz, Patricia Janella; Chere-Quiñónez, Byron Fernando (International Journal of Energy Economics and Policy, 2024)
The article provides an empirical analysis on the impact of renewable energy development on the unemployment rate, agricultural output and relative rural population in Ecuador. Using an empirical approach, the study examined how the production and consumption of this energy affects the labor market in rural regions. To this end, relevant data on the development of renewable energies in the context of Ecuador were collected, and statistical analyses were carried out to evaluate the relationships between these and the variables of interest. The results obtained indicate that the development of renewable energies has can reduce the unemployment rate and has a positive effect on the relative population of rural regions, however, it does not seem to significantly affect agricultural production. These findings support the idea that the production and consumption of renewable energies can generate jobs directly, due to the need for workers for the construction and maintenance of these technologies, and indirectly, through cheaper energy, increased productive efficiency and better conditions for the expansion of companies. The study offers a significant contribution to the field of energy economics in developing countries and highlights the importance of the adoption of renewable energy sources for rural regions.